Compost Solid-phase Microbial Fuel Cell (CSMFC) Performance using Graphene and Graphite as Electrodes - Putri, Soraya Annisa; Confera, Akbar Nugroho; Syafrudin, Syafrudin; Ramadan, Bimastyaji Surya (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Organic waste is a type of waste produced by many sector, which need to managed appropriately. During its development, composting is one of the organic waste management efforts that is often be applied, Another alternative organic waste management in the form of Microbial Fuel Cell (MFC) has emerged. Several researchers conducted studies on MFC performance which was influenced by many factors, especially the electrode which contributes to the electron transfer process. This study has a concern about energy optimization through CSMFC technology using different electrodeâ€™s material. Electrode materials from Graphene and Graphit has good electro-conductivity and has a large surface area, making it suitable for bacteria to adhere. The sampled reactors are consists of two types of electrodesÂ  in the form of graphite and graphene. Each materials has anode and cathode ratio of 1:1, 2:1, and 3:1. The samples measured into three kinds, which called a mature compost measurement, electrochemical measurement, and biochemical measurement. Some collected sampling data were then processed and analyzed statistically using SPSS software. The processed and analyzed data included the calculation of power density, total N, C/N ratio, and moisture content. Any data like voltage (V) and electric current (I) are needed to obtain a power density. The highest average voltage, current, power and power density are produced by the N3 reactor (graphene 3:1) that is 269 x 10-3 V, 163 x 10-6 A, 56 x 10-6 Watt and 1.914 x 10-3 W / m2. There is no significant effect of variations in the type of electrode (graphite and graphene) on CSMFC performances.